2021
DOI: 10.1002/htj.22136
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and economic analysis of energy storage‐based single‐slope solar still with hollow‐finned absorber basin

Abstract: The paucity of drinking water is an alarming glitch across the globe. The conversion of available seawater into drinking water by utilizing renewable energy is the best way to surmount this challenge. Desalination through solar still is one of the notable, monetary, and viable processes among various desalination approaches. The current research aims to augment the potable water yield of single‐slope solar still by using a hollow‐finned absorber basin inserted into paraffin wax—phase change material (PCM). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…The primary objective of the economic assessment is to evaluate the cost per liter (CPL) per one m 2 area of the solar still. The cost analysis is assessed as below 31–33 …”
Section: Thermo‐economic Analysismentioning
confidence: 99%
“…The primary objective of the economic assessment is to evaluate the cost per liter (CPL) per one m 2 area of the solar still. The cost analysis is assessed as below 31–33 …”
Section: Thermo‐economic Analysismentioning
confidence: 99%
“…It was noticed that the integration of hollow fins enhanced the productivity by 43% whereas the productivity of solar still with both fins and energy storage improved the freshwater productivity by 101.5% relative to the productivity of CSS. (Suraparaju et al 2021;Suraparaju and Natarajan 2021a) studied the influence of absorber basin with bottom solid fins and hollow fins inserted in energy storage (paraffin wax) on the freshwater yield of solar still. It was found that the solar still with solid finned absorber inserted in energy storage enhanced productivity by 24.26% compared to CSS.…”
Section: The Role Of Design Parameters In Productivity Enhancementmentioning
confidence: 99%
“…The instantaneous thermal efficiency of the passive solar still is calculated by using the following formula (Kabeel & Abdelgaied 2016;Suraparaju et al 2021)…”
Section: Thermal Analysismentioning
confidence: 99%